Implementasi Sistem Informasi Penggajian Pegawai Berbasis Website Menggunakan Native PHP (Studi Kasus Universitas Jenderal Soedirman) - Wulandari, Kenty Nur; Briandoko, Singgih; Andayani, Mury (Teknikom: Teknologi Informasi, Ilmu Komputer dan Manajemen; Vol 10 No 1 (2025), 2025)
This final project report discusses the implementation of a web-based employee payroll information system using the native PHP programming language, with a case study at Jenderal Soedirman University. The previous payroll system still uses a manual process that is less efficient and has the potential to cause errors in managing employee salary data. Therefore, a system is designed that can assist the staffing department in managing employee data, calculating salaries automatically, and producing payroll reports periodically. The method used in developing this system is the waterfall method which includes the stages of needs analysis, system design, implementation, testing, and maintenance. This system was built using native PHP and MySQL database, employee data management, allowanc, and generation of payroll reports every month. The implementation results show that the developed system is able to simplify and speed up the payroll process, reduce recording errors, and provide easy access to information for related parties. Thus, this system can be a digital solution that supports a more effective and efficient employee payroll administration process in the University environment.